FORTIFICATION OF BUCK WHEAT FOR IMPROVEMENT IN SAFETY AND QUALITY OF “KULCHA”: A TRADITIONAL KASHMIRI BAKED PRODUCT - QURAAZAH AKEEMU AMIN; HAFIZA AHSAN; OWSEEF.A.WANI; QAZI NISSAR (The Bioscan, 2015)
Composite flour was prepared by adding 5,10,15,20 % buck wheat flour to fancy clear wheat flour for develop- ing Kulcha. The processed product was stored for 50 days to ascertain the changes in safety and quality. Incorporation of 20% buckwheat flour provided best nutritional quality by depicting highest protein (9.41%), fat (23.97%), fiber (6.75%) and lowest moisture (2.42%).The diameter of kulcha gradually decreased (73.90 to 73.15 mm) and thickness increased (11.38 to 11.44 mm) thereby decreasing the spread ratio (6.493 to 6.394). The safety stability significantly increased with increasing buck wheat levels. At 50 days of storage 20% fortifica- tion of buckwheat showed lowest fungal count of 3.301 logcfu/g as compared to 3.668 logcfu/g wherein no buckwheat was added. AWRC and FFA also showed highest values of 55.50% and 0.050% in product prepared with 20% buckwheat flour. In contrary to it the maximum incremental cost benefit ratio was 1.50 in flour combination (wheat: buckwheat flour %; 95:5)